Molecular characterization of human enteric viruses in food, water samples, and surface swabs in Sicily - Giuseppa Purpari; Giusi Macaluso; Santina Di Bella; Francesca Gucciardi; Francesco Mira; Patrizia Di Marco; Antonio Lastra; Eskild Petersen; Giuseppina La Rosa; Annalisa Guercio (International Journal of Infectious Diseases, 2019)
Objectives: Enteric viruses are responsible for foodborne and waterborne infections affecting a large number of people. Data on food and water viral contamination in the south of Italy (Sicily) are scarce and fragmentary. The aim of this study was to evaluate the presence of viral contamination in food, water samples, and surface swabs collected in Sicily Methods: The survey was conducted on 108 shellfish, 23 water samples (seawater, pipe water, and torrent water), 52 vegetables, one peach and 17 berries, 11 gastronomic preparations containing fish products and/or raw vegetables, and 28 surface swabs. Hepatitis A virus (HAV), genogroup GI, GII, and GIV norovirus (NoV), enterovirus (EV), rotavirus (RoV), hepatitis E virus (HEV), adenovirus (AdV), and bocavirus (BoV) were detected by nested (RT) PCR, real-time PCR, and sequence analysis. Results: The most frequently detected viruses in shellfish were HAV (13%), NoV (18.5%), and EV (7.4%). Bocavirus was found in 3.7%, HEV in 0.9%, and AdV in 1.9% of the molluscs. Of the 23 water samples, 21.7% were positive for GII NoV and 4.3% for RoV and HEV genotype 3. Of the 70 vegetable samples, 2.9% were positive for NoV GI (GI.5 and GI.6), 2.9% for EV, and 1.4% for HEV. In the gastronomic preparations, only one EV (9%) was detected. No enteric viruses were detected in the berries, fruit, or swabs analyzed. Conclusions: Molecular surveillance of water and food samples clearly demonstrated that human pathogenic viruses are widely found in aquatic environments and on vegetables, and confirmed the role of vegetables and bivalve molluscs as the main reservoirs. Keywords: Enteric virus, PCR, Genotyping, Shellfish, Waters, Vegetables